Prediction of phase separation in a T-Junction - Saieed, A. (Elsevier Inc., 2018)
Despite its modest construction, T-junctions have been used as a partial phase separator in various industries for decades. To this date, the prediction of phase maldistribution at a pipe junction is a serious concern, as oftentimes very high liquid carryovers are received, affecting the operation of downstream equipment. This not only results in unforeseen maintenance, but also in the loss of operational time and cost. To address this matter, a study is reported in which experiments were conducted on five distinct diameter ratio T-junctions under stratified-wavy and slug flow conditions. From the collected data, six numerical correlations were prepared to estimate the side arm extraction of gas and liquid, as well as the pressure at main and side arm outlets of the T-junction. It was found that predictions from present equations concede reasonably well with the experimental results. Â© 2018 Elsevier Inc.